2020
DOI: 10.3390/ijms21176284
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysate Supports Efficient Expansion and Stability of Wharton’s Jelly Mesenchymal Stromal Cells via Active Uptake and Release of Soluble Regenerative Factors

Abstract: Manufacturing of mesenchymal stromal cell (MSC)-based therapies for regenerative medicine requires the use of suitable supply of growth factors that enhance proliferation, cell stability and potency during cell expansion. Human blood derivatives such as human platelet lysate (hPL) have emerged as a feasible alternative for cell growth supplement. Nevertheless, composition and functional characterization of hPL in the context of cell manufacturing is still under investigation, particularly regarding the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In previous studies, we have shown that CM from FBS-cultured BMSC contains several growth factors and cytokines with antiapoptotic and antioxidant properties, including platelet-derived growth factor (PDGF) and vascular endothelial growth factor A (VEGFA), and enhances in vitro osteogenic differentiation of MSC ( Al-Sharabi et al, 2014 ; Al-Sharabi et al, 2016 ; Saleem et al, 2021 ). In context, HPL also contains several growth factors and cytokines, including PDGF, epidermal growth factor (EGF), insulin-like growth factor (IGF), transforming growth factor (TGF), FGF2, stem cell-growth factor-beta (SCGF), interleukin (IL)-1β, IL-2, -6, -10, -12p70, and IL-17A, tumor necrosis factor (TNF)-α and interferon (IFN) ( Cañas-Arboleda et al, 2020 ; Shanbhag et al, 2020a ). Therefore, it is reasonable to postulate that CM of HPL-cultured MSC would be correspondingly more enriched.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that CM from FBS-cultured BMSC contains several growth factors and cytokines with antiapoptotic and antioxidant properties, including platelet-derived growth factor (PDGF) and vascular endothelial growth factor A (VEGFA), and enhances in vitro osteogenic differentiation of MSC ( Al-Sharabi et al, 2014 ; Al-Sharabi et al, 2016 ; Saleem et al, 2021 ). In context, HPL also contains several growth factors and cytokines, including PDGF, epidermal growth factor (EGF), insulin-like growth factor (IGF), transforming growth factor (TGF), FGF2, stem cell-growth factor-beta (SCGF), interleukin (IL)-1β, IL-2, -6, -10, -12p70, and IL-17A, tumor necrosis factor (TNF)-α and interferon (IFN) ( Cañas-Arboleda et al, 2020 ; Shanbhag et al, 2020a ). Therefore, it is reasonable to postulate that CM of HPL-cultured MSC would be correspondingly more enriched.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that it can be a useful biological material for stem cell engineering and regenerative medicine [ 76 ]. Similarly, Caas-Arboleda et al verified that hPL is an appropriate supply of factors that support the survivability, stability, and potency of WJ-MSC, offering significant possibilities for the development of effective regenerative medicine [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] and Cañas-Arboleda et al . [ 16 ]. Umbilical cord fragments were washed in 0.9% saline solution with 10,000 U/mL 1% penicillin/streptomycin, and umbilical veins, arteries, and outer membranes were removed.…”
Section: Methodsmentioning
confidence: 99%